2014
DOI: 10.1386/jaah.4.3.247_1
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing the arts as tools for medicine and public health

Abstract: The arts are often neglected in the context of modern medicine. However, they offer opportunities for greater patient understanding, improved patient comfort and treatment results, and enhanced clinical skills, personal enrichment, and resilience in medical practitioners. The application of the arts to medicine can be categorized into five main categories: medical education, prescriptive options, improved patient experience, public health and care for medical personnel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The art experiences discussed by Christenson (2013) and also Karkabi and Castel (2013) do not canvass artistic embodied practices such as process drama. They do, however, draw attention to ways in which engagement with the arts can provide 'medicine with a personal context', which for students, is a pathway to deeper understanding.…”
Section: A Review Of the Relevant Literaturementioning
confidence: 99%
“…The art experiences discussed by Christenson (2013) and also Karkabi and Castel (2013) do not canvass artistic embodied practices such as process drama. They do, however, draw attention to ways in which engagement with the arts can provide 'medicine with a personal context', which for students, is a pathway to deeper understanding.…”
Section: A Review Of the Relevant Literaturementioning
confidence: 99%
“…The importance of medical clowning is in part highlighted by research findings about the benefits of humor and laughter. This effort largely comes out of the recent positive psychology movement to increase the study of the factors that lead to increased psychological well-being and human strength [10]. Research has shown laughter can increase immune function [11] lower blood pressure [12] and produce weight loss [13] Medical clowning, or simply the increased use of humor by physical therapists themselves, could clearly have many positive effects on health.…”
Section: Positive Psychology: Increasing Innovation In Healthcare Delmentioning
confidence: 99%
“…[5][6][7] Research findings suggest that medical practitioners benefit greatly and empathy is increased when the arts are included in their clinical training. [8][9][10][11] The authors believe that this concept can be translated to pharmacy students in training as well. The inclusion of the arts in healthcare is being addressed increasingly more often, as can be seen in the work being done in groups like the National Organization for Arts in Health (NOAH) and Americans for the Arts.…”
Section: Introductionmentioning
confidence: 99%